KEY TYPES AND CORE PRINCIPLES OF EFFECTIVE LANGUAGE ASSESSMENT (International Conference on Economics, Finance, Banking and Management, 2025)
This article examines the fundamental approaches to language assessment and their underlying principles. It explores how different assessment types serve various educational purposes and identifies critical features that contribute to assessment validity, reliability, and usefulness in both classroom and standardized testing contexts.